Assessing the Natural Source Zone Depletion of a Petroleum-Contaminated Clayey Soil Site in Southern China Combining Concentration Gradient Method and Metagenomics - Zhe Xu; Min Zhang; Zhuo Ning; Ze He; Fenge Zhang (Life, 2024)
Natural source zone depletion (NSZD) is the main process of LNAPL (Light Non-Aqueous Phase Liquid) removal under natural conditions. The NSZD rates assessed ranged from 0.55 to 11.55 kg·m−2·a−1 (kilograms per square meter per year) in previous studies. However, most of these data were obtained from sandy sites, with few clayey sites. To gain knowledge of NSZD in clayey soil sites, the study assessed the NSZD of a petroleum hydrocarbon-contaminated clayey soil site in China, combining the concentration gradient method with metagenomic sequencing technology. The results show that the abundance of methane-producing key enzyme mcrA gene in the source zone was more abundant than in background areas, which suggests that there was methanogenesis, the key process of NSZD. The concentration gradients of oxygen and carbon dioxide existed only in shallow soil (<0.7 m), which suggests that there was a thin methane oxidation zone in the shallow zone. The calculated NSZD rates range from 0.23 to 1.15 kg·m−2·a−1, which fall within the moderate range compared to previous NSZD sites. This study expands the knowledge of NSZD in clayey soil and enriches the attenuation rate data for contaminated sites, which is of significant importance in managing petroleum contaminants.